Community-based comprehensive measures to prevent severe fever with thrombocytopenia syndrome, China. (August 2018) - Wang, Yuchao; Li, Kefeng; Li, Peng; Sun, Jimin; Ye, Ling; Dai, Yaxin; Tang, An; Jiang, Jianmin; Chen, Can; Tong, Zhendong; Yan, Jianbo
Highlights: A feasible solution for the control of severe fever with thrombocytopenia syndrome is presented, which was deployed in some rural villages in China. The comprehensive measures, which included health education and risk communication, weed removal, livestock management, and tick control, were performed and evaluated. Based on the above strategy and the practice in pilot areas, the actual numbers of cases and of infected villages were obviously lower than the values predicted in time-series models using per-month data from previous years. Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging disease caused by the SFTS virus (SFTSV) of the family Bunyaviridae . Since the virus was first isolated in 2009, it has become widespread in China, with an increasing number of cases year on year. Although the disease has been researched extensively in past years, there are still no effective measures to suppress the epidemic situation. This article reports a pilot study of comprehensive measures, including health education and risk communication, weed removal, livestock management, and tick control, to prevent this emerging disease in an endemic region of China. The density of ticks decreased dramatically month by month after acaricides were sprayed in the areas surrounding recreational and agricultural settings. The number of SFTS cases and villages involved declined in the years after the integrated measures were applied. Comprehensive measures, especially community-based tick control, may be a promising means of preventing SFTS in endemic regions.